2014
DOI: 10.1534/genetics.114.172049
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Role for the Zinc-Finger Transcription Factor EGL-46 in the Differentiation of Gas-Sensing Neurons in Caenorhabditis elegans

Abstract: Oxygen (O 2 ) and carbon dioxide (CO 2 ) provoke distinct olfactory behaviors via specialized sensory neurons across metazoa. In the nematode C. elegans, the BAG sensory neurons are specialized to sense changes in both O 2 and CO 2 levels in the environment. The precise functionality of these neurons is specified by the coexpression of a membrane-bound receptor-type guanylyl cyclase GCY-9 that is required for responses to CO 2 upshifts and the soluble guanylyl cyclases GCY-31 and GCY-33 that mediate responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Because other studies have shown that the TEA domain transcription factor EGL-44 typically functions in concert with EGL-46 to specify cell-specific traits in C. elegans (Rojo Romanos et al, 2015; Wu et al, 2001; Yu et al, 2003), we tested an egl-44 mutant for PVD defects. This experiment revealed that the 2° branching defect of egl-44 is virtually identical to that of egl-46 (p>0.05, one-way ANOVA with Tukey’s multiple comparison test) and also results in a modest but significant reduction (~25%) in PVD 2° branches (p<0.001 vs wt, one-way ANOVA with Tukey’s multiple comparison test) (Figure 1e and Supplemental Figure 1e).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because other studies have shown that the TEA domain transcription factor EGL-44 typically functions in concert with EGL-46 to specify cell-specific traits in C. elegans (Rojo Romanos et al, 2015; Wu et al, 2001; Yu et al, 2003), we tested an egl-44 mutant for PVD defects. This experiment revealed that the 2° branching defect of egl-44 is virtually identical to that of egl-46 (p>0.05, one-way ANOVA with Tukey’s multiple comparison test) and also results in a modest but significant reduction (~25%) in PVD 2° branches (p<0.001 vs wt, one-way ANOVA with Tukey’s multiple comparison test) (Figure 1e and Supplemental Figure 1e).…”
Section: Resultsmentioning
confidence: 99%
“…Experiments with additional PVD-specific markers are needed to validate this hypothesis. The strong conservation of MEC-3-related LIM homeodomain proteins and of EGL-44 and EGL-46 in vertebrate genomes argues that similar transcriptional networks may regulate neuronal morphogenesis in the brain (Anbanandam et al, 2006; Desai et al, 1988; Feng et al, 2013; Hunter and Rhodes, 2005; Rojo Romanos et al, 2015; Rosenbaum et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the population behavioral assay, we describe in this protocol how these changes of speed are measurable to enable evaluation of the gas-sensing capability of a population of worms. We have previously used these assays to determine the functional importance of multiple transcription factors required for the development of gas-sensing neurons in C. elegans (Brandt et al , 2012; Gramstrup Petersen et al , 2013; Rojo Romanos et al , 2015 and 2017). In Figure 6, we illustrate examples of results obtained: we show how wild type worms decrease their speed in response to a BAG neuron-mediated downshift (21%-10%) or a URX neuron-mediated upshift (10%-21%) in O 2 concentration (Figure 6A).…”
Section: Discussionmentioning
confidence: 99%
“…15, 16 More recently, EGL-13 and EGL-46 were also found to be important for the differentiation of the CO 2 -sensing BAG neurons. 17,18 Further studies are required to fully understand the molecular mechanisms induced by high levels of CO 2 and how these mechanisms regulate physiologic responses to elevated CO 2 . We discuss here our recent study of a previously uncharacterized behavioral response of C. elegans to elevated CO 2 , and a new component that is involved in C. elegans CO 2 signaling.…”
Section: Introductionmentioning
confidence: 99%